2019
DOI: 10.1080/09500693.2019.1647473
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the teacher: exploring STEM graduate students’ nature of science conceptions in a teaching methods course

Abstract: Teaching is the one profession that creates all other professions. -Author Unknown COURSE INFORMATION ASTR 8500/BIOL 7110 Mondays 3:30-4:45, PLSB 300 COURSE MATERIALS All readings will be provided. Recommended books (for those of you interested in learning more about teaching, learning, and course design): Buskist, W., & Benassi, V. A. (2011). Effective college and university teaching: Strategies and tactics for the new professoriate. Sage. Chalmers, A. F. (2013). What is this thing called science?. Hackett Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
2
9
0
1
Order By: Relevance
“…Students with science-religion who have the most positive perspective on Darwinian evolution [40]. Students' opinions about science-religion and found that students were interested in exploring both, but did not have the intellectual tools to do [41]. Learning that relates religion to science must be involved in every moral, affective and spiritual dimension of students to reject the conflict between science and religion [42].…”
Section: Ethnoscience and Its Relationship With Religious Sciencesmentioning
confidence: 99%
“…Students with science-religion who have the most positive perspective on Darwinian evolution [40]. Students' opinions about science-religion and found that students were interested in exploring both, but did not have the intellectual tools to do [41]. Learning that relates religion to science must be involved in every moral, affective and spiritual dimension of students to reject the conflict between science and religion [42].…”
Section: Ethnoscience and Its Relationship With Religious Sciencesmentioning
confidence: 99%
“…This work is uncomfortable and time‐intensive, which may impede widespread implementation of inclusive teaching across institutions (DiAngelo & Sensoy, 2010; Lombardi et al., 2011). Additionally, many science instructors hold the assumption that STEM fields are somehow “unbiased” and immune to societal injustices (Saini, 2020; Smith & Scharmann, 1999; Wheeler et al., 2019), making inclusive teaching challenging. Lastly, traditional STEM curricula tend to promote racist, sexist, and Eurocentric ideas (Black Lives Matter in Ecology & Evolution, 2020; Hayssen, 2020; Hayssen & Orr, 2017; Peters, 2015; Smedley & Smedley, 2005; Vakil & Ayers, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This work is uncomfortable and time-intensive, which may impede widespread implementation of inclusive teaching across institutions (DiAngelo & Sensoy, 2010;Lombardi et al, 2011). Additionally, many science instructors hold the assumption that STEM fields are somehow "unbiased" and immune to societal injustices (Saini, 2020;Smith & Scharmann, 1999;Wheeler et al, 2019) Smedley & Smedley, 2005;Vakil & Ayers, 2019). Disparities start early, as a recent study found introductory biology textbooks were more likely to highlight men scientists, and none of the books analyzed highlighted a Black woman scientist (Wood et al, 2020).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…Por otro lado, existe un conjunto de investigaciones desarrolladas, sobre cómo las personas científicas profesionales perciben sus procesos de hacer trabajo en ciencias mientras realizan sus investigaciones; sin embargo, se sabe poco acerca de cómo el estudiantado de postgrado percibe la naturaleza de la producción de conocimiento científico a lo largo de sus carreras, por ejemplo (Blaney et al, 2020;Cumming, 2009;Delamont y Atkinson, 2001;Delamont et al, 2000;Maher et al, 2019;Wheeler et al, 2019). Para interpretar los resultados de este estudio se utilizaron los conceptos teóricos de la NdeC, dados por una visión de ciencia abierta/pública, estas con el conjunto de visiones menos sofisticadas e ingenuas de la NdeC y ciencia cerrada/ privada, un conjunto de visiones más o altamente sofisticadas de la NdeC derivada del trabajo de Elkana (2000).…”
Section: Introductionunclassified